“PAY DAY” FOR ILLEGAL FOREIGNERS Rahim v The Minister of Home Affairs (965/2013) [2015] ZASCA 92 (29 May 2015) - Darren Subramanien (Obiter, 2016)
People from across the African continent continue to make their way to South Africa to escape violence and poverty in their own countries. South Africa is also seen as a beacon of stability and economic growth on the continent. There has been growing concern that the illegal influx of foreigners in search of a better life, and the failure by the South African Government to control its porous borders, have led to a high degree of animosity and resentment, directed at foreigners. International law and South African law affirm that South Africa is a constitutional state that subscribes to the principle of legality, an incident of the rule of law. It is against this backdrop that The Supreme Court of Appeal (SCA) handed down a landmark ruling in Rahim v The Minister of Home Affairs ((965/2013) [2015] ZASCA 92 (29 May 2015)), where the Court awarded damages to illegal immigrants who were illegally held by the Department of Home Affairs, following a failure by the Department to designate a proper holding facility for non-citizens in South Africa. One of the implications of this judgment is that the Department will have to conduct a proper determination of holding facilities so as not to be liable for claims such as the one in the present case.